Interactions entre parametres agronomiques et economiques dans la recherche agrostologique - Kaufmann, Ralph R. von; Mohamed-Saleem, M.A. (1989)
Highlights the interactions between agronomy and economics in developing forage production techniques for the two main land-use situations in the subhumid zone of Nigeria, viz, cultivation and fallow. Presents break-even sorghum grain-stylo price ratios for different undersowing times, capital and recurrent costs of a 4-ha fodder bank with metal fencing, and costs of obtaining crude protein from a 4-ha fodder bank and from cotton-seed cake. Summarises effect of dry-season supplementation on the productivity of Bunaji cattle under traditional management and the economic returns on fodder banks over 10 years. Presents crop-forage planting patterns used.